2006
DOI: 10.1016/j.rapm.2005.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Transforaminal Injection and the Radicular Artery: Variation in Anatomical Location Within the Cervical Intervertebral Foramina

Abstract: A larger population is necessary to characterize the range of anatomic variations in arterial supply within the foramina. Available studies support the current technique of fluoroscopic needle insertion. Yet, there is wide anatomic variation in the origin and location of these vessels, and even with strict adherence to technique, it is feasible that a properly placed needle could penetrate a radicular artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 10 publications
0
51
0
Order By: Relevance
“…We typically avoid transforaminal dispersal of contrast with SCNRB and do not routinely perform transforaminal cervical epidural steroid injections. The posterior aspect of the lateral foramen is considered safest with regard to potential radicular artery branches; however, anatomic studies have concluded that radicular feeding arteries may be found at any aspect of the cervical foramen, 21,22 supporting the need for real-time observation of contrast injection.…”
Section: Discussionmentioning
confidence: 99%
“…We typically avoid transforaminal dispersal of contrast with SCNRB and do not routinely perform transforaminal cervical epidural steroid injections. The posterior aspect of the lateral foramen is considered safest with regard to potential radicular artery branches; however, anatomic studies have concluded that radicular feeding arteries may be found at any aspect of the cervical foramen, 21,22 supporting the need for real-time observation of contrast injection.…”
Section: Discussionmentioning
confidence: 99%
“…Only one artery out of eight to ten reaches the spinal cord [10]. From the intervertebral foramina aspect, five radicular arteries (C5, C6, two at C7, C8) enter the foramina, either anteriorly or posteriorly, to supply the anterior and posterior spinal arteries [22].…”
Section: The Radiculomedullary Arteriesmentioning
confidence: 99%
“…The radicular arteries arise from the vertebral artery, ascending cervical artery and deep cervical artery and typically lie close to the nerve roots [19]. In a study by Hoeft et al, the radicular branches of the vertebral artery have their course at the antero-medial aspect of the neural foramen [20]. The ascending or deep cervical arteries may course across the entire foramen and may also be damaged or inadvertently injected during attempted transforaminal approach [20].…”
Section: Review Gofeld and Montgomerymentioning
confidence: 99%
“…In a study by Hoeft et al, the radicular branches of the vertebral artery have their course at the antero-medial aspect of the neural foramen [20]. The ascending or deep cervical arteries may course across the entire foramen and may also be damaged or inadvertently injected during attempted transforaminal approach [20]. Narouze et al studied US-guided cervical nerve root injections with confirmatory fluoroscopy [21].…”
Section: Review Gofeld and Montgomerymentioning
confidence: 99%